Implantação e análise de um sistema fotovoltaico conectado à rede de 10,72 kWp com sistema de armazenamento de energia na UTFPR - Souza, Adriana Schilive de (2021)
With the growing penetration of intermittent renewable energy sources in the Brazilian energy mix, like the photovoltaic, which in 2021 has exceeded the mark of 11GW of installed capacity, the interest for energy storage systems has increased. Such systems add flexibility in the supply and demand of energy, providing services to the production, transmission, distribution and consumers, which have the main characteristic the quick response to requests. In this context, this work presents the phases of deployment and analysis of a 10.72 kWp Grid Connected Photovoltaic System integrated to a storage system using lead-acid batteries at the Universidade Tecnológica Federal do Paraná, Neoville branch, in Curitiba PR. Aiming at the development of energy management strategies, the system was initially developed to support the demand, by storing energy during periods of lower kWh ratings and then using that energy in the on-peak periods (from 18h to 21h), when the ratings are higher, thus optimizing costs. The proposed methodology aims at attenuating the demand curve by inserting the photovoltaic generation and controlling the energy storage system discharge. The first month of operation of the system, May 2020, resulted in a reduction of 1.04% in the energy consumption at the off-peak periods and 1.01% reduction at the on-peak periods. The avoided cost was approximately R$881.96. The results are promising, considering that the development of the utilization of this technology in Brazil is in its initial stages.